2008
DOI: 10.1073/pnas.0802659105
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin-dependent kinase inhibitor p57kip2 is a negative regulator of Schwann cell differentiation and in vitro myelination

Abstract: The p57kip2 gene encodes a member of the cyclin-dependent kinase inhibitor family, proteins known to block G 1/S transition during the mammalian cell cycle. We observed that expression of p57kip2 in Schwann cells of the developing and injured adult peripheral nervous system is dynamically regulated. Using gene knockdown by means of vector-based RNA interference in cultured primary Schwann cells we found that reduced levels of p57kip2 lead to cell cycle exit, actin filament stabilization, altered cell morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 41 publications
5
58
1
Order By: Relevance
“…An expression-level-dependent role for p57Kip2 in Notch-regulated oligodendrocyte specification in the ventral spinal cord has been suggested from elegant experiments in zebrafish, 34 and it was recently shown that proper levels of p57Kip2 is critical for correct proliferation as well as differentiation of primary oligodendrocyte progenitor cells as well as Schwann cells. 36,37 Furthermore, the timing and levels of Mash1 and Dlx1/2 expression, as well as Notch signaling, have been shown to be critical parameters to secure the proper proliferation, differentiation, and migration of ventral telencephalic progenitors. 24,38 It is at present difficult experimentally to yield efficient oligodendrocyte production from embryonic NSCs hampering such investigations in NSCs, but future studies should address this hypothesis in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…An expression-level-dependent role for p57Kip2 in Notch-regulated oligodendrocyte specification in the ventral spinal cord has been suggested from elegant experiments in zebrafish, 34 and it was recently shown that proper levels of p57Kip2 is critical for correct proliferation as well as differentiation of primary oligodendrocyte progenitor cells as well as Schwann cells. 36,37 Furthermore, the timing and levels of Mash1 and Dlx1/2 expression, as well as Notch signaling, have been shown to be critical parameters to secure the proper proliferation, differentiation, and migration of ventral telencephalic progenitors. 24,38 It is at present difficult experimentally to yield efficient oligodendrocyte production from embryonic NSCs hampering such investigations in NSCs, but future studies should address this hypothesis in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclin-dependent kinase inhibitor p57kip2, which is downregulated as postnatal nerves myelinate, has also been implicated in negative regulation of myelination, since RNA interference-based knockdown of p57kip2 in cultured Schwann cells induces modest expression of myelin proteins, including P 0 and MBP, and promotes myelination in co-cultures (Heinen et al, 2008).…”
Section: Other Agents Implicated In Negative Regulation Of Myelinationmentioning
confidence: 99%
“…However, silencing RNA (siRNA) dependent approaches led only to transient suppression of p57kip2 expression. As an alternative, we used a small hairpin RNA (shRNA) cassette (19), which allows long-term p57kip2 suppression and was previously shown to be specific for p57kip2 and free from off-target effects, such as an IFN response induction (19). By using this approach, oligodendroglial p57kip2 expression could be reduced for up to 9 days as shown by quantitative RT-PCR of transfected and sorted OPCs 2 days following transfection ( Fig.…”
Section: Regulation Of P57kip2 Expression In Cultured Oligodendrogliamentioning
confidence: 99%
“…As a member of the cip/kip family, p57kip2 was originally described as a cyclin-dependent kinase inhibitor (CDKI), but a number of other cellular processes were recently shown to depend on cip/kip proteins (18). For instance, long-term suppression of p57kip2 in Schwann cells, the myelinating glial cells of the PNS, efficiently induces their differentiation in culture, even in the absence of axons (19). We therefore investigated the impact of down-regulated p57kip2 levels on oligodendroglial maturation and report here that this results in acceleration of cellular differentiation in vitro.…”
mentioning
confidence: 99%